Presença do ideário católico na Revista do Ensino de Minas Gerais (1925-1940) - Coelho, Monalisa Lopes dos Santos (2021)
This study is part of the research line History and Historiography of Education of the Postgraduate Program in Education of the Universidade Federal de Uberlândia PPGED-UFU. The object of study is the presence of elements of the Catholic creed in the Revista do Ensino de Minas Gerais between the years 1925 and 1940. The problematization of the object was projected in the historical context of the first half of the 20th century (Republic, State-Church split, movement of Catholic restoration and the New School). It was questioned how the Catholic Church managed to conquer space in the Revista do Ensino? What and how were the catholic religious contents conveyed by this periodical? Did such contents contribute or help to compose a catholic-christian teaching and pedagogy? The general objective is to understand the nuances of how the Catholic Church managed to remain active and influential in the field of education after the decree of Brazil as a secular state; and the specific objectives are to characterize the catholic pedagogical contents published in Revista do Ensino; To understand what the Pedagogy of Jesus Christ and the New Christian School were in the publication; to recognize how the contents with a Catholic background legitimized teaching as synonymous with mission, vocation, destiny, sacrifice, priesthood, and the place of women. This research is documental and bibliographic, and as a historical study, it followed the theoretical and methodological postulates and procedures of the dialectical historical materialism method, concerning itself with the contradictions, conflicts, clashes, antagonisms in the existing relations between the macro and the micro, that is, between the national and the local. The central historical source was the Revista do Ensino de Minas Gerais with the examination of 175 issues in the period 1925-1940, and complementary sources such as papal encyclicals, pastoral letters, official and Catholic newspapers, laws, decrees, and the epoch book Minas Gerais in 1925. The analytical categories were: Pedagogy of Jesus Christ, New Christian School, and teaching as synonymous with: mission, vocation, destiny and priesthood, and the place of women. Chapter 1 contextualizes the early republican period in Brazil, discusses the separation between the State and the Catholic Church, the catholic restoration movement, and the New School movement, in which the historical-political-educational-religious conjuncture is characterized. Chapter 2 focuses on Minas Gerais, dealing with the Minas Gerais catholic tradition, and the Church's involvement with successive state governors. Reflections are made on the Francisco Campos reform, teacher training, the genesis of the Revista do Ensino created in 1892 and reactivated in 1925, characterizing the historical-political-educational-religious conjuncture in this state, and its reverberations in this pedagogical press. Chapter 3 brings the analysis of the research data, examines covers and the speeches of ecclesiastical and educational authorities of Minas Gerais conveyed in the print, based on the general survey of publications linked to Catholicism (1925-1940) and the graph derived from the survey; the principles of the Pedagogy of Jesus Christ are analyzed, and how the pedagogical contents recommended teaching to the female figure. The results pointed out that the Catholic Church gathered forces and established a movement of reaction to the secular school, and in Minas Gerais, the clergy found not only a society of conservative catholic tradition, but also successive state governments willing to accept the collaboration of the Church in the directions of education. With this opening, the Church could count on the Revista do Ensino to convey its pedagogical creed, including its postulates of the New Christian School, to reach teachers, elementary school teachers, and schoolmistresses, under a discourse that urged educators to follow the Master Jesus Christ, and to face teaching as an earthly mission, self-sacrificing, sacrificing, as priestesses in the quality of teachers, accepting a low remuneration, but caring more about performing well the sacred pedagogical mission.